(untitled) - Paáarinho, A.M.=700 1 Leandro, M.J.; Oliveira, M.; Figueiredo, E.; Franco, J.C.; Neves-Martins, J.; Mexia, A.
(Pt, En, Es)
ilus., 14 ref.
Avaliacao do parasitismo por Anagyrus pseudococci (Girault) em cochonilhas-algodao em proteaceas
Keywords: INSECTA; PARASITISMO; ENCAPSULACION; CONTROL BIOLOGICO; ESPAÑA; ANAGYRUS PSEUDOCCOCI; PARACOCCUS; DELOTTOCOCCUS